Iraq as a Lab: a Critique of the New American Way of War - Fischer Friedman, Marcela; Ferabolli, Silvia Regina (Revista Brasileira de Estudos de Defesa, 2021)
This paper analysis the evolution of the US force structure after 1975 in two core aspects: foreign policy and military modernization. Building on the works of Clausewitz (2003) and Mearsheimer (1981), we argue that a country's force structure should be based mainly on foreign policy considerations. The evolution of the US Army followed this logic until its defeat in Vietnam (1975), but this traumatic event precipitated reforms in the US military force before a proper reformulation of the country’s foreign policy objectives had been achieved. Therefore, these reforms created a "syndrome" that would deform and reform the US strategic culture inadequately. The new military doctrine, Air-Land Battle (ALB) was not oriented towards long-term political objectives, but rather by purely operational and tactical issues of combat, which proved harmful for the US interests in the long-run. Hence, we propose to analyze the Iraq Wars (1991-2003) as labs for this New American Way of War, the first empirical applications of ALB. We conclude by demonstrating that the disregard for post-war planning ended up forcing a prolonged and costly American involvement in the Middle East and damaging the country’s international image.